2017
DOI: 10.3389/fpls.2017.00493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TIFY Family Genes and Analysis of Their Expression Profiles in Response to Phytohormone Treatments and Melampsora larici-populina Infection in Poplar

Abstract: The TIFY domain contains approximately 36 conserved amino acids that form the core motif TIF[F/Y]XG, and they were reported to play important roles in plant growth, tissue development and defense regulation. Moreover, more and more evidence has shown that some members of the TIFY gene family perform their functions by modulating plant hormone signaling pathways. Poplar trees are found worldwide, and they comprise approximately 30 species. Benefit from the importance of poplar and its advanced platform, this tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
(59 reference statements)
3
40
0
Order By: Relevance
“…WGD is one of the important mechanisms of species evolution, producing new genomic regions and making it more complex and diverse [63]. Similar conditions have been found in other species, such as 19 of the 24 poplar TIFY genes produced by WGD [64]. The large proportion of duplicated genes in the TIFY family revealed that WGD made a large contribution to the generation of the TIFY gene family.…”
Section: Discussionmentioning
confidence: 55%
“…WGD is one of the important mechanisms of species evolution, producing new genomic regions and making it more complex and diverse [63]. Similar conditions have been found in other species, such as 19 of the 24 poplar TIFY genes produced by WGD [64]. The large proportion of duplicated genes in the TIFY family revealed that WGD made a large contribution to the generation of the TIFY gene family.…”
Section: Discussionmentioning
confidence: 55%
“…TIFY is a plant-specific transcription factor that has been identified in many model plants, such as Arabidopsis, Rice, and Maize [1,3,5]. Previous studies have given a comprehensive analysis of 24 PtrTIFY genes in leaves of P. trichocarpa under various phytohormone treatments and abiotic stresses [19,20]. In this study, we found a new PtrTIFY gene, PtrJAZ13, that belongs to the important JAZ subfamily.…”
Section: Discussionmentioning
confidence: 81%
“…In summary, different TIFY subfamily members have different functions during plant growth and development, as well as different responses to phytohormone treatment and abiotic stress.Populus trichocarpa serves as a model forest species and is widely used in forest tree genomics studies [18]. Previous works identified 24 PtrTIFY genes in the P. trichocarpa genome and analyzed their expression profiles under JA, MeJA, SA, salt, cold stresses, and pathogen infection in leaves [19,20]. In our study, besides these 24 genes, we found a new TIFY family member in the P. trichocarpa genome; because of the existence of the Jas and TIFY motif, we named it PtrJAZ13.…”
mentioning
confidence: 99%
“…According to the results of gene sequence identity and protein domain conservation analyses, 38 BjJAZ genes were identified in the genome of tuber mustard, and the number of BjJAZs is more than double that in Arabidopsis (13), rice (15) and Brachypodium distachyon (15) [27][28][29]. The reason might be that tuber mustard is an allotetraploid species formed by hybridization between the diploid ancestors of Brassica rapa and Brassica nigra with subsequent genome duplication [30]; genome duplication is also found in moso bamboo, the genome of which contains 18 PeJAZ genes [31].…”
Section: Discussionmentioning
confidence: 99%